Description of trihalomethane levels in three UK water suppliers - Whitaker, Heather; Nieuwenhuijsen, Mark J; Best, Nicola; Fawell, John; Gowers, Alison; Elliot, Paul (Journal of exposure analysis and environmental epidemiology, 2003)
Samples of drinking water are routinely analysed for four trihalomethanes (THMs), which are indicators of by-products of disinfection with chlorine, by UK water suppliers to demonstrate compliance with regulations. The THM data for 1992–1993 to 1997–1998 for three water suppliers in the north and midlands of England were made available for a UK epidemiological study of the association between disinfection by-products and adverse birth outcomes. This paper describes the THM levels in these three supply regions and discusses possible sources of variation. THM levels varied between different suppliers' water, and average THM levels were within the regulatory limits. Chloroform was the predominant THM in all water types apart from the ground water of one supplier. The supplier that distributed more ground and lowland surface water had higher dibromochloromethane (DBCM) and bromoform levels and lower chloroform levels than the other two suppliers. In the water of two suppliers, seasonal fluctuations in bromodichloromethane (BDCM) and DBCM levels were found with levels peaking in the summer and autumn. In the other water supplier, chloroform levels followed a similar seasonal trend whereas BDCM and DBCM levels did not. For all three water suppliers, chloroform levels declined throughout 1995 when there was a drought period. There was a moderate positive correlation between the THMs most similar in their structure (chloroform and BDCM, BDCM and DBCM, and DBCM and bromoform) and a slight negative correlation between chloroform and bromoform levels.